'She come like a sister to me': a qualitative study of volunteer social support for disadvantaged women in the transition to motherhood in England - McLeish, J; Redshaw, M (Royal Society, The, 2021)
This qualitative study explores the ways in which disadvantaged women benefit from social support from a trained volunteer during pregnancy and the postnatal period, using the theoretical frameworks of stress and coping and a multi-dimensional model of social support. Forty-seven mothers took part in semi-structured interviews. The mothers, who had received social support through nine volunteer projects in England, faced many potentially stressful challenges besides having a baby (such as poverty, poor housing, histories of abuse, motherhood at a young age, living with physical or mental health difficulties, migration and insecure immigration status). Analysis was in two distinct stages: first, an inductive thematic analysis of mothers' experiences, and second, mapping of the results onto the theoretical frameworks chosen. Volunteers built relationships of trust with mothers and gave skilled emotional support, positive appraisal support, informational support and practical support according to mothers' individual needs, thereby assisting mothers exposed to multiple stressors with problem-focused, emotion-focused and perception-focused coping. This helped to reduce social isolation, increase effective access to services and community resources, and build mothers' confidence, self-esteem and self-efficacy. Volunteer social support may have particular salience for mothers who lack structural support and need skilled functional support. This article is part of the theme issue 'Multidisciplinary perspectives on social support and maternal-child health'.